2009
DOI: 10.1111/j.1432-2277.2008.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Anderson-Fabry disease: a case-finding study among male kidney transplant recipients in Austria

Abstract: Summary The diagnosis of Anderson–Fabry disease is often delayed or even missed. As severe renal manifestations are a hallmark of alfa‐galactosidase A (AGAL) deficiency, we tested the hypothesis that Anderson–Fabry disease is under‐recognized among male kidney transplant recipients. This nation‐wide study in Austria enrolled 1306 patients (ca 65% of all kidney transplanted males) from 30 kidney centers. AGAL activity was determined from filter paper dried blood spots by a fluorescence assay. A positive screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
(32 reference statements)
2
22
2
1
Order By: Relevance
“…The FD prevalence estimated in the present study was 0.19% and after algorithm was considered, prevalence increased to 0.87%, was close to that previously reported [10-20]. Studies performed in Brazil by Marinho et al in 2007 reported an FD prevalence of 0.52% for the city of Natal in the state of Rio Grande do Norte and Vale et al found 0.57% in the state of Piauí [13, 14].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The FD prevalence estimated in the present study was 0.19% and after algorithm was considered, prevalence increased to 0.87%, was close to that previously reported [10-20]. Studies performed in Brazil by Marinho et al in 2007 reported an FD prevalence of 0.52% for the city of Natal in the state of Rio Grande do Norte and Vale et al found 0.57% in the state of Piauí [13, 14].…”
Section: Discussionsupporting
confidence: 74%
“…Even though more men were screened, there were more women with FD in the population. This is in contrast with previous reports that FD is more prevalent in men [8, 10-15]. We believe that women are not screened because the diagnostic test for women consists of a more expensive DNA analysis versus that in men, an enzyme measurement that is less expensive [4].…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…vyrų). 2009 m. nacionalinė patikra Austrijoje pakartota ir nustatyti dar 2 anksčiau nediagnozuoti atvejai [15]. Prieš metus ir Lietuvoje pradėta dializuojamų pacientų patikra dializės centruose, laukiama tyrimo rezultatų.…”
Section: Diskusijaunclassified